(untitled) (Studia Prawnicze / The Legal Studies, 2013)
Sądownictwo arbitrażowe bywa często określane jako „wymiar sprawiedliwości dla gentlemanów”, co skłaniać może do refleksji o niewystępowaniuw jego toku problemów proceduralnych o tak istotnym znaczeniu dla wynikunsprawy, jak w przypadku postępowań toczonych przed sądami powszechnymi. Praktyka pokazuje tymczasem, iż w postępowaniach arbitrażowych nieco różni się jedynie rodzaj spornych kwestii procesowych, podczas gdy ich wpływ na ostateczne rozstrzygnięcie także jest znaczący. Spośród kwestii formalnych najważniejsze znaczenie wydaje się przy tym odgrywać status arbitrów orzekających w sprawie. Arbitration is frequently described as “justice for gentlemen”, which can suggest an absence of procedural issues of such significance to the outcome of the case as in the case of proceedings before common courts. Meanwhile, experience shows that only the types of disputed procedural issues differ slightly in arbitration, while their impact on the outcome is also significant. Of the formal issues, the most important seems to be the status of the arbitrators adjudicating in the case. Given that, in practice, arbitration is of a single instance and has a limited, exhaustively itemized number of premises specified in Article 1206 of the Civil Procedures Code for lodging a complaint to set aside an arbitral award, strict adherence by arbitrators to the principles of impartiality and independence is of fundamental importance. A possible breach of these principles can undermine the confidence of the parties not only in the arbitral panel in a specific case, but also in arbitration in general. Consequently, a possible attempt to remove an arbitrator, as a rule, constituting the manifestation of efforts to eliminate errors made while the arbitral panel was being constituted, is considered only a partial remedium. Therefore, the objective of the study is to analyse the key formal expectations of arbitrators, as well as consider selected issues related to the institution of the removal of an arbitrator - understood as a guarantee of his impartiality and independence. The intention of this analysis is to help define the status of an arbitrator in arbitration proceedings.